2015
DOI: 10.1007/s10608-015-9710-8
|View full text |Cite
|
Sign up to set email alerts
|

Combining tDCS and Working Memory Training to Down Regulate State Rumination: A Single-Session Double Blind Sham-Controlled Trial

Abstract: Rumination has been associated with reduced working memory and dorsolateral prefrontal cortex activity. This study explored whether single session anodal transcranial direct current stimulation (tDCS) applied to the dorsolateral prefrontal cortex and/or working memory training can transiently ameliorate working memory and down regulate state rumination. Sixty-six participants were randomly allocated to three conditions: (1) control training ? tDCS, (2) working memory training ? sham tDCS and (3) working memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Previous studies have reported evidence that working memory improvements are correlated with the administration of tDCS in diverse contexts (Grafman et al, 1994 ; Nitsche et al, 2003 ; Dockery et al, 2009 ; McKendrick et al, 2015 ). Specifically, tDCS over DLPFC was associated with acute increases in working memory accuracy (Stagg and Johansen-Berg, 2013 ; Chhatbar and Feng, 2015 ; De Putter et al, 2015 ; Santarnecchi et al, 2015 ). Although, we observed a reduction in learning rate variance from tDCS to the right DLPFC in the n-back task, but did not find an increase in working memory accuracy for tDCS of either the DLPFC or M1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported evidence that working memory improvements are correlated with the administration of tDCS in diverse contexts (Grafman et al, 1994 ; Nitsche et al, 2003 ; Dockery et al, 2009 ; McKendrick et al, 2015 ). Specifically, tDCS over DLPFC was associated with acute increases in working memory accuracy (Stagg and Johansen-Berg, 2013 ; Chhatbar and Feng, 2015 ; De Putter et al, 2015 ; Santarnecchi et al, 2015 ). Although, we observed a reduction in learning rate variance from tDCS to the right DLPFC in the n-back task, but did not find an increase in working memory accuracy for tDCS of either the DLPFC or M1.…”
Section: Discussionmentioning
confidence: 99%
“…For WM training, we used an adaptive n-back paradigm 3 , 70 72 . Stimuli were presented using the open-source software Brain Workshop v4.8.4 73 and PsychoPy2 v1.80.04 74 .…”
Section: Methodsmentioning
confidence: 99%
“… Klingberg (2010) has indicated that the working memory capacity of individuals is not constant and can be improved by training. Given the foundation role of working memory for various advanced cognitive functions ( von Bastian and Oberauer, 2014 ), the benefits of training are not only limited to the memory capacity itself but can be transfer to distant fields such as fluid intelligence ( Au et al, 2015 , Jaeggi et al, 2008 ) and more relevant to our concern, emotional fields, such as facilitating emotional execution ( Schweizer et al, 2011 , Schweizer et al, 2013 ); improving affective processing ( Li et al, 2016 ), enhancing self-regulation ( De Putter et al, 2015 , Xiu et al, 2016 , Xiu et al, 2018 ), and promoting mood states ( Pan et al, 2018 , Takeuchi et al, 2014 ). Particularly, a few studies have dealt with the effects of working memory training on rumination ( Onraedt et al, 2014 , Wanmaker et al, 2015 ), but failed to find positive effects of working memory training on self-reported rumination level.…”
Section: Introductionmentioning
confidence: 99%